(3GdfLjHjGJs - (3GdfLjH GdSeQbfOj , eMeO Hf Ydj Hf YeQ GdSeQbfOj, fLjH GdOjf CHh MGeO,J (B619 (3g` s ((3eMeO Hf CHj HcQ GdfjSGHhQi s)
(3ChdgG (B:s
(3GdMeO ddg Ydi fYeGFg GdSGHbI , hGjGOjg GddGMbI Efi bO LeYJ dCLdi ai gPg GdeLdOI eG cGfJ MGLJi Edjg GVWQGQGjI YfO eTGgOI GdeQV heYGdLJge ,dJchf OGFekG Hjf jOi CfXQ ajgG hCSJZfi HgG Yf GdfXQ ai cJH TJi s
(3BNQgG (B:s
(3YV GdCQHYI hGdCQHYjf hYdGLg hQHeG cai ajg GSJYeGd GdedM hGdNd Ydi ehVY GdYVI s
(3fSNI QGHYI cGdSGHbIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B280 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B31s
(3agQS GdWH (B- (3U (B195 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B267 s
Keywords: (3GdWHs